Liming and priming: the long-term impact of pH amelioration on mineralisation may negate carbon sequestration gains. - Samantha P. Grover; Clayton R. Butterly; Xiaojuan Wang; Deirdre B. Gleeson; Lynne M. Macdonald; Caixian Tang (Soil Security, 2021)
Acidity negatively impacts upon soil capability and conditions across approximately 50% of the world's arable land. Plant growth and nutrient cycling are known to respond positively to the addition of lime to decrease soil acidity. However, the interactions between liming and soil carbon dynamics remain incompletely understood. The nexus of soils, food security and climate change make this topic an urgent concern for investigation. This study utilised soils (Cambisols) from three long-term lime field trials (13-39 years) on farms. Soils (0-10 cm) were incubated in the laboratory for 3 months with and without 13C-labelled wheat crop residue. This approach enabled direct quantification of the CO2-C originating from three different processes; decomposition of extant soil organic carbon (SOC), decomposition of the added crop residue, and SOC priming i.e. the additional decomposition of SOC stimulated by addition of plant material. Biological and chemical soil properties were also quantified, with a novel application of measurement of the abundance of the functional genes involved in SOC decomposition. Priming was significantly increased in limed soils (P<0.01). The abundance of both archaeal rRNA genes, and the laccase-like functional gene involved in lignin decomposition correlated significantly and positively with SOC priming (Rho 0.46, P<0.01). Decomposition of extant SOC was positively correlated with pH and N (Rho 0.65, P<0.001). Decomposition of the added crop residue was also correlated with pH and inorganic N, albeit less strongly than for SOC (Rho 0.43, P< 0.05). These results support the theory that the application of lime to ameliorate soil acidity improves conditions for soil microorganisms as well as for plants. Archaea, and organisms harbouring SOC-decomposing laccases, would appear to play a key role in releasing nutrients stored in extant SOC, when priming is prompted by the addition of new plant material. This work highlights the importance of taking account of multiple response factors when assessing potential solutions within the food security-climate change nexus.